Zadłużenie powiatów ziemskich województwa śląskiego w latach 2004-2007 - Czempas, Jan; Rduch, Renata (Indebtedness of counties in Silesian Voivodeship in 2004-2007, 2010)
The aim of the paper is to present the scale and dynamics of indebtedness related to incomes of all 17 counties in Silesian Voivodeship. On the basis of concentration ratio proposed by K. Kukuła, the authors assess changes in incomes' and indebtedness' distribution. The period taken into consideration during the analysis spanned from 2004 to 2007. The authors indicated the usefulness of the concentration ratio for the assessment of indebtedness' stability
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2010, Nr 8 (14), s. 7-24
Keywords: powiat; zadłużenie; county; indebtedness